THE EFFECT OF DIFFERENT DOSES OF MULTIFLORA HONEY ON MALE BETTA FISH (Betta splendens) SEED PRODUCTION - Gumelar, Tedi; Rina, Rina; Farkhan, Muhammad; Zaidy, Azzam Bachur (Jurnal Perikanan Unram, 2025)
Multiflora honey contains potassium and flavonoids that play a role in changing fish sexuality from female to male. One factor that influences the success of sex direction is the dosage. This study aims to obtain the right dosage of multiflora honey in the formation of male sex (masculinization). This study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. Observation of male sex was carried out after 60 days of maintenance by observing the urogenital organs and 70 days of maintenance with gonad histology using HE staining. The results showed that the highest percentage of males was obtained at a dose of 4 mg/L.